Targeting Polyamine Oxidase to Prevent Excitotoxicity-Induced Retinal Neurodegeneration - Pichavaram, Prahalathan; Palani, Chithra Devi; Patel, Chintan; Xu, Zhimin; Shosha, Esraa; Fouda, Abdelrahman Y.; Caldwell, Ruth B.; Narayanan, Subhadra Priya (Frontiers in Neuroscience, 2019)
Dysfunction of retinal neurons is a major cause of vision impairment in blinding diseases that affect children and adults worldwide. Cellular damage resulting from polyamine catabolism has been demonstrated to be a major player in many neurodegenerative conditions. We have previously shown that inhibition of polyamine oxidase (PAO) using MDL 72527 significantly reduced retinal neurodegeneration and cell death signaling pathways in hyperoxia-mediated retinopathy. In the present study, we investigated the impact of PAO inhibition in limiting retinal neurodegeneration in a model of NMDA (N-Methyl-D-aspartate)-induced excitotoxicity. Adult mice (8-10 weeks old) were given intravitreal injections (20 nmoles) of NMDA or NMLA (N-Methyl-L-aspartate, control). Intraperitoneal injection of MDL 72527 (40 mg/kg body weight/day) or vehicle (normal saline) was given 24 h before NMDA or NMLA treatment, and continued until the animals were sacrificed (varied from 1-7 days). Analyses of retinal ganglion cell (RGC) layer cell survival was performed on retinal flatmounts. Retinal cryostat sections were prepared for immunostaining, TUNEL assay and retinal thickness measurements. Fresh frozen retinal samples were used for Western blotting analysis. A marked decrease in the neuronal survival in the RGC layer was observed in NMDA treated retinas compared to their NMLA treated controls, as studied by NeuN immunostaining of retinal flatmounts. Treatment with MDL 72527 significantly improved survival of NeuN positive cells in the NMDA treated retinas. Excitotoxicity induced neurodegeneration was also demonstrated by reduced levels of synaptophysin and degeneration of inner retinal neurons in NMDA treated retinas compared to controls. TUNEL labelling studies showed increased cell death in the NMDA treated retinas. However, treatment with MDL 72527 markedly reduced these changes. Analysis of signaling pathways during excitotoxic injury revealed the downregulation of pro-survival signaling molecules p-ERK and p-Akt, and the upregulation of a pro-apoptotic molecule BID, which were normalized with PAO inhibition. Our data demonstrate that inhibition of polyamine oxidase blocks NMDA-induced retinal neurodegeneration and promotes cell survival, thus offering a new therapeutic target for retinal neurodegenerative disease conditions.